2016
DOI: 10.1093/nar/gkw483
|View full text |Cite
|
Sign up to set email alerts
|

G9a promotes proliferation and inhibits cell cycle exit during myogenic differentiation

Abstract: Differentiation of skeletal muscle cells, like most other cell types, requires a permanent exit from the cell cycle. The epigenetic programming underlying these distinct cellular states is not fully understood. In this study, we provide evidence that the lysine methyltransferase G9a functions as a central axis to regulate proliferation and differentiation of skeletal muscle cells. Transcriptome analysis of G9a knockdown cells revealed deregulation of many cell cycle regulatory genes. We demonstrate that G9a en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 56 publications
9
51
1
Order By: Relevance
“…53 This demonstrates an added level of complexity in Ehmt2's regulation of p53, and that its function as a repressor or co-activator is likely context dependent. This context-dependent activity also extends to the p53 target gene p21, where Ehmt2 is required to both epigenetically repress, 16,43 and activate 46 expression. This suggests that Ehmt2 may be a core co-regulator of the p53 pathway, being involved in both repressing p53 when not activated, and a co-activator of the p53-dependent stress response pathway once stimulated.…”
Section: Ehmt2 In Cell Cycle Regulationmentioning
confidence: 81%
See 1 more Smart Citation
“…53 This demonstrates an added level of complexity in Ehmt2's regulation of p53, and that its function as a repressor or co-activator is likely context dependent. This context-dependent activity also extends to the p53 target gene p21, where Ehmt2 is required to both epigenetically repress, 16,43 and activate 46 expression. This suggests that Ehmt2 may be a core co-regulator of the p53 pathway, being involved in both repressing p53 when not activated, and a co-activator of the p53-dependent stress response pathway once stimulated.…”
Section: Ehmt2 In Cell Cycle Regulationmentioning
confidence: 81%
“…29 However, H3K9me2 has been implicated in the terminal commitment of blood, cardiac, retinal, neural, muscle and germline lineages. 23,25,29,[40][41][42][43] For example, H3K9me2 plays a dynamic role in retinal progenitor cells 44 and loss of Ehmt2 mediated epigenetic repression leads to profound defects in the early retina. Zebrafish ehmt2 morphants show severe decreases in crx, neuroD and irbp gene expression; markers of retinal cell differentiation.…”
Section: Canonical Roles Of Ehmt1/2 Complexmentioning
confidence: 99%
“…In this regard, it has been reported that, in undifferentiated myoblasts, H3K9me2 represses the promoters of some MyoD target genes, such as the muscle-specific gene myogenin 59 and the cell cycle exit genes Cdkn1a (coding for the cdk inhibitor p21 cip1 ) and Rb1. 52 In the case of myogenin promoter, the molecular mechanism of repression would involve the interference with the activity of chromatin-bound MyoD through the cooperation with other histone modifications. 60 It has also been reported that G9a, in addition to methylate histone H3, also methylates the MyoD protein, 61 indicating that the relationship between G9a, H3K9me2, and MyoD functions is very complex.…”
Section: Discussionmentioning
confidence: 99%
“…We focused our attention on H3K9me2, a modification catalyzed by G9a and G9a-like methyltransferases 51 , which have been recently recognized to play important roles in myoblast proliferation and differentiation. 52 In addition, H3K9me2 and DNA methylation are known to be coordinated by a complex and bidirectional relationship involving the recognition of DNA methylation by the histone methylation machinery, and vice versa. 53 Furthermore, treatment with DNA demethylating agents was reported to cause reduction of H3K9me2 (but not H3K9me3) levels at different regulatory regions.…”
Section: Responsive and Unresponsive Cells Exhibit Differential H3k9mmentioning
confidence: 99%
“…55 Gene expression studies using microarrays indicate that G9a targets an array of cell cycle genes. 27,56 G9a overexpressing cells progress faster into the S phase, and, conversely, G9a knockdown leads to lower S phase cells compared with controls. 27,57 In cultured myoblasts, G9a promotes proliferation via 2 different mechanisms.…”
mentioning
confidence: 91%